2020
DOI: 10.5267/j.ac.2020.1.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of non-performing loans on profitability of commercial banks: Case of Vietnam

Abstract: Profit always be the top priority of banking operation over the years. Commercial banks maximize the net interest margin by charging more interests to the borrowers and offering lower interests to the depositors. Their aggressive lending strategies can sometimes result in credit risk, moral hazard and non-performing loans. Some studies found that non-performing loans have negative impact on the bank's profitability; some argued otherwise. This paper aims at investigating the impact of non-performing loans on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 14 publications
(17 reference statements)
0
10
0
3
Order By: Relevance
“…Some previous studies present that among the crucial factors affecting NPL are economic growth, which negatively correlates with the NPL and NPF. Similar studies have found that macroeconomic factors have a significant relationship with NPL and NPF (Alzoubi, 2017;Do et al, 2020). Khemraj & Pasha (2009) stated GDP with a negative impact, but interest rate, inflation, forex, and excessive lending positively correlate with the increase of NPL and NPF.…”
Section: Introductionmentioning
confidence: 56%
“…Some previous studies present that among the crucial factors affecting NPL are economic growth, which negatively correlates with the NPL and NPF. Similar studies have found that macroeconomic factors have a significant relationship with NPL and NPF (Alzoubi, 2017;Do et al, 2020). Khemraj & Pasha (2009) stated GDP with a negative impact, but interest rate, inflation, forex, and excessive lending positively correlate with the increase of NPL and NPF.…”
Section: Introductionmentioning
confidence: 56%
“…In contrast, after controlling for ownership concertation and listing status, Umar and Sun (2018) do not find results comparable to Bashir et al (2017). More recently, Do et al (2020) evaluate the effect of NPLs on the profitability of commercial banks in Vietnam during 2008–2017. Their findings show that, when the NPL rate increases, the ability of banks to profit decreases.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Peneliti kedepannya disarankan mengambil tambahan variabel bebas layaknya non performing loan dan asset quality agar dapat menguji adanya pengaruh variabel tersebut terhadap variabel profitabilitas bank (Do et al, 2020).…”
Section: Saran Teoritisunclassified